Absence of integrin-mediated TGFβ1 activation in vivo recapitulates the phenotype of TGFβ1-null mice - Yang, Zhiwei (The Rockefeller University Press, 2007)
The multifunctional cytokine transforming growth factor (TGF) β1 is secreted in a latent complex with its processed propeptide (latency-associated peptide [LAP]). TGFβ1 must be functionally released from this complex before it can engage TGFβ receptors. One mechanism of latent TGFβ1 activation involves interaction of the integrins αvβ6 and αvβ8 with an RGD sequence in LAP; other putative latent TGFβ1 activators include thrombospondin-1, oxidants, and various proteases. To assess the contribution of RGD-binding integrins to TGFβ1 activation in vivo, we created a mutation in Tgfb1 encoding a nonfunctional variant of the RGD sequence (RGE). Mice with this mutation (Tgfb1(RGE/RGE)) display the major features of Tgfb1(−/−) mice (vasculogenesis defects, multiorgan inflammation, and lack of Langerhans cells) despite production of normal levels of latent TGFβ1. These findings indicate that RGD-binding integrins are requisite latent TGFβ1 activators during development and in the immune system.